2009
DOI: 10.1038/ijo.2009.144
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Lp(a) during weight reduction in obese children is modified by the apo(a) kringle-IV copy number variation

Abstract: Background: Lipoprotein(a) [Lp(a)] is considered an independent risk factor for cardiovascular disease. Its concentration is mainly determined by the kringle-IV repeat copy number variation (CNV) at the apolipoprotein(a) [apo(a)] locus. Objective: We aimed to investigate the immediate effect of weight reduction on plasma Lp(a) levels and its dependency on the apo(a) CNV in obese children. Design: We performed a prospective longitudinal intervention study of a low-fat hypocaloric diet conducted in a 3-week diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Finally, Brandstatter el al. 32 observed that after a 3-week hypocaloric diet in children, a 6.6% decrease in body weight leads to ~ 20% decrease in Lp(a) levels, which is comparable to the decline seen in LDL-C and triglycerides. These findings suggest that BMI is strongly related to Lp(a) and that ethnicity may affect this relationship.…”
Section: Discussionmentioning
confidence: 71%
“…Finally, Brandstatter el al. 32 observed that after a 3-week hypocaloric diet in children, a 6.6% decrease in body weight leads to ~ 20% decrease in Lp(a) levels, which is comparable to the decline seen in LDL-C and triglycerides. These findings suggest that BMI is strongly related to Lp(a) and that ethnicity may affect this relationship.…”
Section: Discussionmentioning
confidence: 71%
“…Known obesogenic factors such as physical activity and food intake have been shown to account for a significant portion of the variance in BMI with estimates ranging 5–10% (Chambers and Swanson 2010; Newby et al 2006; French et al 1994; Jebb and Moore 1999). Additionally, research is beginning to elucidate G×E affecting BMI (Rampersaud et al 2008; Lappalainen et al 2009; Qi et al 2008; Brandsttter et al 2009; Razquin et al 2010). At least two genes included in the current GRSS show evidence for G×E effects.…”
Section: Discussionmentioning
confidence: 99%
“…Rare variants could have considerable effects in singular individuals. Another, yet unexplored possibility is the influence of CNVs, which are involved in the genetic predisposition to common diseases or quantitative phenotypes [14]. GIANT found that the SNP most strongly associated with BMI was linked to a 45-kb deletion polymorphism [15].…”
Section: Discussionmentioning
confidence: 99%